La Acrópolis de Cantona : proceso de desarrollo de su estructura urbana / Yadira Martínez Calleja. - Martínez Calleja, Yadira (Colección Arqueología. Serie Logos., 2018)
The Acropolis of Cantona is the first book that explains the development process of the urban structure of one of the largest and most complex prehispanic cities of northeastern region of the Central Altiplano of Mexico, from the first evidence of settelments to its abandonment, taking as an example the most important civic-religious center of the city. For this, the author analyzes the urban-architectonic characteristics as well as the natural environment, from which derive the production of food, litica and ceramic artifacts, and compares them with those of other contemporary societies, mainly from the Bajío region, to build interesting hypotheses about the ethnico-cultural identity of the inhabitants and builders of Cantona, in the state of Puebla, Mexico. After more than ten centuries of the abandonment of this great metropolis (and 30 years of its uninterrupted exploration) this work leads us to understand it as the tacit and highly emblematic demonstration of the indomitable spirit of the inhabitants of one of the most aggressive and reluctant natural spaces, transforming it into extraordinary cultural center and one of the most representative Prehispanic sites of Mesoamerica.